2023
DOI: 10.1186/s12887-023-04028-8
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between cognitive functioning and physical fitness in regard to age and sex

Abstract: The aim of this study was to analyze the relationships among physical cognitive ability, academic performance, and physical fitness regarding age and sex in a group of 187 students (53.48% male, 46.52% female) from one town of Norwest of Jaén, Andalusia (Spain), aged between 9 and 15 years old (M = 11.97, SD = 1.99). The D2 attention test was used in order to analyze selective attention and concentration. Physical fitness, reflected on maximal oxygen uptake (VO2max), was evaluated using the 6 min Walking Test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…However, our findings suggest that only vigorous and very vigorous levels of physical activity seem to impact ∆CP. This aligns with previous studies on the types of PA, such as sports [22,25] and aerobic and anaerobic exercise [40], which predominantly involve higher intensities that can improve CP. Despite the results obtained, Jeppesen, et al [46] advocate for light-intensity PA. Future interventions aimed at enhancing CP and, subsequently, academic performance ought to consider strategies that encourage vigorous and very vigorous PA.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, our findings suggest that only vigorous and very vigorous levels of physical activity seem to impact ∆CP. This aligns with previous studies on the types of PA, such as sports [22,25] and aerobic and anaerobic exercise [40], which predominantly involve higher intensities that can improve CP. Despite the results obtained, Jeppesen, et al [46] advocate for light-intensity PA. Future interventions aimed at enhancing CP and, subsequently, academic performance ought to consider strategies that encourage vigorous and very vigorous PA.…”
Section: Discussionsupporting
confidence: 90%
“…However, research on adolescents from low socioeconomic status has suggested that gender serves as a predictor of cognitive pathways, with CP improving in boys over time while decreasing in girls [ 39 ]. Conversely, a study conducted on adolescents in Spain revealed gender differences, with girls exhibiting stronger CP [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gallotta et al [ 33 ] demonstrated that the effects of high-intensity aerobic exercise on cognitive function were changed or influenced by the exercise duration, intensity, physical fitness, and the particular physical activity conducted during exercise, indicating that high-intensity aerobic exercise appears to be a better at boosting cognitive functioning. Some authors, in fact, have highlighted the impact of high-intensity aerobic exercise in increasing executive function [ 34 , 35 , 36 , 37 ]. Moreover, Du Rietz et al [ 38 ] concluded that 20 min of high-intensity exercise enhanced cognition and attentional resources in adults.…”
Section: Introductionmentioning
confidence: 99%